(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The early detection and prompt treatment of acutely poisoned patients are not just important; they are critical. The medical community, including healthcare providers, researchers, and emergency medicine professionals, play a vital role in improving the chances of survival and recovery in these cases. Objective: To describe the healthcare and treatment provided to patients with acute poisoning within 24 hours of admission to the Center of Emergency and Poison Control, Vietnam National Children’s Hospital, in 2020. Methods: A cross-sectional epidemiological study was conducted on 60 children admitted with poisoning to the Center of Emergency and Poison Control of the National Children’s Hospital from June to July 2020. Results: Most children were under 5 years old (77%), with 53.3% male. Poisoning was primarily caused by food/drinks (46.7%), followed by incidents related to parents (35%). The most common poisons were chemicals (46.7%), drugs (15%), food/insect venom (10%), and opium/methadone (6.7%). Regarding emergency interventions, 21.7% required oxygen, 5% needed endotracheal intubation and mechanical ventilation, 5% received blood transfusions, 78.3% required intravenous electrolyte replacement, and 2 cases needed cardiac arrest resuscitation. Detoxification treatments included gastric lavage in 10% of cases, combined gastric lavage and activated charcoal in 3%, increased diuresis in 10%, and hemodialysis in 2 children. Specific detoxification drugs were used in 21.7% of cases. For care, 38.3% of children had gastric tubes, 8.3% had urinary tubes, 16.7% required sputum suctioning, and 100% were monitored using monitoring machines. In the first 24 hours, 10% had vital signs monitored 12 times or more, and 36.7% were observed 6-11 times. Conclusion: Most pediatric poisoning cases involved children under 5, with food/drink poisoning and parental involvement as critical causes. Ordinary treatments included intravenous fluids, oxygen, and gastric lavage. However, the key to successful treatment and recovery lies in timely monitoring in the first 24 hours, underscoring the vital need for ongoing emergency and poisoning care training for healthcare providers.